EFFECTS OF POWDERED GLASS AS AN ADMIXTURE IN CEMENT CONCRETE BLOCK (Nigerian Journal of Technology, 2018)
This paper investigated the effects of glass usage in finely divided form on the properties of cement concrete. The powdered glass was used as admixture, replacing cement in the concrete production process. The sourced glass were washed and dried for some days. The dried glass was then crushed into smaller pieces before grinding to finely divided form. Replacement of cement with powdered glass was done at 0-10% with 2% increment by weight of cement. Using a design mix of 1:2:4, with a constant water cement ratio of 0.6, the workability of fresh specimens were determined using the slump height procedure. The specimens were then poured in 150x150x150mm steel moulds and left for 24 hours. The hardened concrete specimens were cured by complete immersion in water for 7, 14, 21 and 28 days. The result showed that workability increases with increase in admixture content. It further revealed that the compressive strength increases with admixture addition to about 4% powdered glass addition. The compressive strength at 6% addition of powdered glass was also higher than that of the conventional concrete. Thus replacement can be done to about 6% addition of powdered glass by weight of cement. The models developed from the study corroborated well with experimental values as high coefficient of determination values were obtained. The models can thus, be used to predict the compressive strength of powdered glass-cement concrete. http://dx.doi.org/10.4314/njt.v38i1.2